2004
DOI: 10.2214/ajr.182.3.1820663
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Biliary Stones:Sphincteroplasty and Occlusion Balloon for the Clearance of Bile Duct Calculi

Abstract: Percutaneous anterograde evacuation of bile duct stones with dilatation of the papilla using an angioplasty catheter and assisted with an occlusion balloon to expel the calculi is a cost-effective, nontraumatic, and safe procedure that retains the anatomic and functional integrity of the sphincter. It is a viable alternative procedure in the treatment of bile duct lithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
2
30
0
1
Order By: Relevance
“…However, percutaneous techniques have also been used for extrahepatic biliary stones via a T-tube sinus tract or percutaneous transhepatic tract. [183][184][185][186] High rates of successful duct clearance (90%-100%) using a variety of techniques have consistently been reported with percutaneous approaches. [183][184][185][186][187][188][189][190][191] However, severe bleeding events have been reported in as many as 14% of patients with percutaneous transhepatic approaches, with mortality as high as 8%.…”
Section: Percutaneous Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…However, percutaneous techniques have also been used for extrahepatic biliary stones via a T-tube sinus tract or percutaneous transhepatic tract. [183][184][185][186] High rates of successful duct clearance (90%-100%) using a variety of techniques have consistently been reported with percutaneous approaches. [183][184][185][186][187][188][189][190][191] However, severe bleeding events have been reported in as many as 14% of patients with percutaneous transhepatic approaches, with mortality as high as 8%.…”
Section: Percutaneous Managementmentioning
confidence: 99%
“…[183][184][185][186] High rates of successful duct clearance (90%-100%) using a variety of techniques have consistently been reported with percutaneous approaches. [183][184][185][186][187][188][189][190][191] However, severe bleeding events have been reported in as many as 14% of patients with percutaneous transhepatic approaches, with mortality as high as 8%. 184,188 Given the logistical complexity (percutaneous tracts take time to mature), incidence of severe complications, and available alternatives, percutaneous techniques for managing extrahepatic bile duct stones are not recommended as a first-line strategy.…”
Section: Percutaneous Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous transhepatic removal of CBD stones is a minimally invasive alternative for surgical treatment. This approach is not commonly used for patients in whom ERCP treatment is not possible and only a few studies have reported the results of this procedure [17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…One patient in our series was treated by balloon dilatation of the sphincter of Oddi through the transcystic route. [12][13][14] The balloon catheter is inserted through the supraumbilical port site. Incision on the cystic duct should not be more than one-third of its circumference to avoid avulsion of the cystic duct during retraction.…”
Section: Discussionmentioning
confidence: 99%